How Emerging Market Leaders Can Spur Technological Gains - Moelders, Florian; Rehermann, Thomas; Hammah, Nana Esi (International Finance Corporation, Washington, DC, 2018)
New technologies help firms in emerging markets make significant gains. But these firms often face barriers to successfully incorporating new technologies into their businesses. Emerging-market leaders, however, can take steps to help firms overcome these barriers, including strengthening regulatory frameworks, improving education, fostering trade, and increasing access to finance.